Construction of a C-reactive protein-albumin-lymphocyte index-based prediction model for all-cause mortality in patients on maintenance hemodialysis - Junmin Huang; Junfeng Hao; Huasheng Luo; Lu Chen; Hongying Luo; Huafeng Liu; Yongzhi Xu; Peng Wang (Renal Failure)
Objective The mortality rate of patients undergoing maintenance hemodialysis (MHD) remains high. The C-reactive protein-albumin-lymphocyte (CALLY) index is a novel biomarker that reflects inflammation, nutritional and immune status, all merged into one single derived parameter. No study has yet linked the CALLY index to survival in hemodialysis. This study aims to explore the correlation between the CALLY index and mortality in MHD patients, and develop and validate a nomogram to estimate the likelihood of death in this population.Methods This retrospective cohort study collected data from 436 patients and they were divided into survival group (n = 335) and non-survival group (n = 101). Multivariate logistic regression analysis was used to screen factors associated with death, and nomograms were developed to estimate the risk of death in MHD patients. The discrimination and calibration of nomograms were validated using the area under the receiver operating characteristic (ROC) curve (AUC) and calibration curve. In the study, stratification analysis and covariate adjustment were conducted to explore the correlation between the CALLY index and the mortality of MHD patients.Results In the final model, logistic regression showed that the CALLY index, creatinine, triglycerides, dialysis duration, absolute neutrophil count, blood urea nitrogen, sodium and ferritin were variables associated with mortality in MHD patients. A nomogram was developed to assess the risk of death in MHD patients. The AUC of the model was 0.821 (95% CI: 0.778–0.861). The results of stratified analysis and calibration model showed that the CALLY index was a protective factor for maintaining the mortality of MHD patients.Conclusions The CALLY index is closely related to the mortality of MHD patients. A nomogram constructed based on CALLY index can effectively evaluate the mortality risk of MHD patients.